2014
DOI: 10.1186/1741-7015-12-7
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between stress and the BDNFVal66Met polymorphism in depression: a systematic review and meta-analysis

Abstract: BackgroundMajor depression is a disabling psychiatric illness with complex origins. Life stress (childhood adversity and recent stressful events) is a robust risk factor for depression. The relationship between life stress and Val66Met polymorphism in the brain-derived neurotrophic factor (BDNF) gene has received much attention. The aim of the present work was to review and conduct a meta-analysis on the results from published studies examining this interaction.MethodsA literature search was conducted using Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(114 citation statements)
references
References 87 publications
(114 reference statements)
4
105
1
4
Order By: Relevance
“…Similar to evidence on low working memory capacity, the met allele of the BDNF Val66Met polymorphism has been associated with impaired responses to stress and heightened vulnerability to depression (e.g., Alexander, Osinsky, Schmitz, Mueller, Kuepper, & Hennig, 2010; Classen, Wells, Knopik, McGeary, & Beevers, 2011; Colzato, Van der Does, Willem, Kouwenhoven, Elzinga, & Hommel, 2011; Gatt et al, 2009; Pandey & Dwivedi, 2009; Pei et al, 2012; Shalev et al, 2009; Vinberg, Trajkovska, Bennike, Knorr, Knudsen, & Kessing, 2009; see also a meta-analysis by Hosang, Shiles, Tansay, McGuffin, & Uher, 2014). The genetic variation in exon 11 of the BDNF gene results in an amino-acid substitution from valine to methionine at codon 66 (Val66Met) and influences BDNF protein production.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Similar to evidence on low working memory capacity, the met allele of the BDNF Val66Met polymorphism has been associated with impaired responses to stress and heightened vulnerability to depression (e.g., Alexander, Osinsky, Schmitz, Mueller, Kuepper, & Hennig, 2010; Classen, Wells, Knopik, McGeary, & Beevers, 2011; Colzato, Van der Does, Willem, Kouwenhoven, Elzinga, & Hommel, 2011; Gatt et al, 2009; Pandey & Dwivedi, 2009; Pei et al, 2012; Shalev et al, 2009; Vinberg, Trajkovska, Bennike, Knorr, Knudsen, & Kessing, 2009; see also a meta-analysis by Hosang, Shiles, Tansay, McGuffin, & Uher, 2014). The genetic variation in exon 11 of the BDNF gene results in an amino-acid substitution from valine to methionine at codon 66 (Val66Met) and influences BDNF protein production.…”
mentioning
confidence: 64%
“…This pattern of findings suggests a differential susceptibility pattern (Roisman, Newman, Fraley, Haltigan, Groh, & Haydon, 2012), and it might explain inconsistencies in past research examining BDNF, stress, and depression. Some past studies found a relation between the BDNF met allele and increased stress reactivity or increased risk for depression in interaction with stress (see the recent meta-analysis by Hosang et al, 2014). Others, however, have found the opposite (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This is a functional SNP that reduces the processing of pro-BDNF to mature BDNF decreases BDNF transport to terminals, and thereby blocks activity dependent release of BDNF. The BDNF Met allele has been associated with reduced hippocampal volume and executive function in humans [28, 29] and increased risk for depression in patients exposed to early life stress or trauma [32, 45, 54]. BDNF Met knock-in mice display a reduction in the number and length of branch points of CA3 pyramidal neurons in the hippocampus (spine density was not examined) [57].…”
Section: Mechanisms Underlying Dendrite and Spine Deficits Caused By mentioning
confidence: 99%
“…Life stresses such as childhood adversity or a recent stressful event, are recognized as being risk factors for depression (Hosang et al. 2014). Notably, the Met allele of BDNF, Val66Met, has been shown to have significant associations with life stress and depression.…”
Section: Introductionmentioning
confidence: 99%